AN IN-SYRINGE La CO-PRECIPITATION METHOD FOR PRE-CONCENTRATION OF OXO-ANIONS FORMING ELEMENTS IN SEAWATER FOLLOWED BY ICP-MS MEASUREMENT - Dwinna Rahmi; Yanbei ZHU; Eiji Fujimori; Takuya Hasegawa; Tomonari Umemura; Shigeji Konagaya; Hiroki Haraguchi (Universitas Andalas, 2007)
Vol. 1 No. 1ABSTRACT A lanthanum (La) co-precipitation method was explored for pre-concentration of oxo-anion forming elements followed by measurement with Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The co-precipitation and subsequent washing and elution steps were performed in a 25 mL-volume syringe in order to save the sample consumption and to avoid the contamination from the experimental environment. In the present work, various parameters such as the concentration of La added into the sample solution, the pH, aging time, and so on were optimized to obtain good recoveries and analytical detection limits for V, As, Se, Sb, and W. Generally, in the co-precipitation method, high concentration of precipitant (in this case, La) causes a serious problem of signal memory effect in ICP-MS measurement. To reduce such memory effect, in the present experiment, high level of La was removed by passing the analyte solution (i.e., lanthanum hydroxide dissolved in 1 M HNO3) through a mini column packed with cation-exchange resins. The method thus obtained was evaluated through the measurement of V, As, Se, Sb and W in seawater reference materials (CASS-4 and NASS-5). The recoveries exceeded 80%, and the observed values were in good agreement with the certified values. Thus, the present method was applied to the determination of trace elements in real seawater sample. Keywords: Lanthanum, pre-concentration